RELATIONSHIP BETWEEN ELECTROLYTE LEVELS OF PREGNANT WOMEN AND THE EVENT OF PREECLAMPSIA - Qanita Wulandara; Siti Patimah (Poltekkes Kemenkes Tasikmalaya, 2022)
Preeclampsia is a condition of high blood pressure accompanied by protein in the urine and become one of the causes of maternal and fetal morbidity and mortality. Electrolytes such as calcium,sodium, potassium and chloride contribute significantly to vascular smooth muscle function and play an important role in the etiopathogenesis of hypertension.This study was conducted to determine the relationship between levels of calcium, sodium, potassium and chloride with the incidence of preeclampsia in pregnant women. The type of research used is an analytic observational study with a case control design. The sample in this study was 80 pregnant women, namely 40 for the case group and 40 for the control group according to the inclusion and exclusion criteria set. Statistical analysis was performed by chi square.In this study, the results showed that there was a relationship between calcium, potassium and chloride levels with the incidence of preeclampsia. It is hoped that this study can increase the knowledge of health workers and become the basis for providing intake of calcium, potassium and sodium levels to prevent preeclampsia.